The Heat Shock Transcription Factor HsfA Is Essential for Thermotolerance and Regulates Cell Wall Integrity in Aspergillus fumigatus - Fabri, João Henrique Tadini Marilhano; Rocha, Marina Campos; Fernandes, Caroline Mota; Persinoti, Gabriela Felix; Ries, Laure Nicolas Annick; Cunha, Anderson Ferreira da; Goldman, Gustavo Henrique; Del Poeta, Maurizio; Malavazi, Iran (Frontiers in Microbiology, 2021)
The deleterious effects of human-induced climate change have long been predicted. However, the imminent emergence and spread of new diseases, including fungal infections through the rise of thermotolerant strains is still neglected, although a potential consequence of global warming. Thermotolerance is a remarkable virulence attribute of the mold Aspergillus fumigatus. Under high-temperature stress, opportunistic fungal pathogens deploy an adaptive mechanism known as heat shock (HS) response controlled by heat shock transcription factors (HSFs). In eukaryotes, HSFs regulate the expression of several heat shock proteins (HSPs), such as the chaperone Hsp90, which is part of the cellular program for heat adaptation and a direct target of HSFs. We recently observed that the perturbation in cell wall integrity (CWI) causes concomitant susceptibility to elevated temperatures in A. fumigatus, although the mechanisms underpinning the HS response and CWI cross talking are not elucidated. Here, we aim at further deciphering the interplay between HS and CWI. Our results show that cell wall ultrastructure is severely modified when A. fumigatus is exposed to HS. We identify the transcription factor HsfA as essential for A. fumigatus viability, thermotolerance and CWI. Indeed, HS and cell wall stress trigger the coordinated expression of both hsfA and hsp90. Furthermore, the CWI signaling pathway components PkcA and MpkA were shown to be important for HsfA and Hsp90 expression in the A. fumigatus biofilms. Lastly, RNA-sequencing confirmed that hsfA regulates the expression of genes related to the HS response, cell wall biosynthesis and remodeling, and lipid homeostasis. Our studies collectively demonstrate the connection between the HS and the CWI pathway, with HsfA playing a crucial role in this cross-pathway regulation, reinforcing the importance of the cell wall in A. fumigatus thermophily.